The effect of purslane seeds on biomarkers of oxidative stress in diabetic patients: A randomized controlled cross-over clinical trial - Zakizadeh, Elahe; Faghihimani, Elham; Saneei, Parvane; Esmaillzadeh, Ahmad (International journal of preventive medicine, 2015)
This study was designed to examine the effects of purslane seeds on biomarkers of oxidative stress in type 2 diabetic patients. This cross-over randomized controlled clinical trial was conducted on 40 patients with type 2 diabetes. Participants were randomly assigned to receive either 10 g/day purslane seeds with 240 cc low-fat yogurt (intervention group) or only 240 cc low-fat yogurt (as a control group) for 5 weeks. After a 2-week washout period, subjects were moved to the alternate arm for an additional 5 weeks. At baseline and end of each study phase, fasting blood samples were collected to quantify biomarkers of oxidative stress. We observed a slight decrease in plasma total antioxidant capacity in both groups, however, between-group changes were not significant (-2.67 vs. -2.95 μg/dL, P = 0.94). Plasma malondialdehyde in purslane group increased slightly, however, we observed no significant effect in the control group (1.62 vs. -0.47 μg/dL, P = 0.58). Although both groups had a slight reduction in plasma oxidized low-density lipoprotein (ox-LDL), we failed to find any significant effect of purslane on plasma ox-LDL (-1.06 vs. -1.71 μg/dL, P = 0.85). This cross-over clinical trial revealed that consumption of purslane seeds for 5 weeks in type 2 diabetic patients did not result in improved oxidative stress.